the The Role of Power BI Applying in Accounting Financial Performance Analysis: An Analytical Study of the Opinions of a Sample of Employees in Industrial Companies in the Kurdistan Region of Iraq - Dlwan Taher Azzat Khan; Rizgar Abdullah sabir Jaf (Zanco Journal of Human Sciences, 2026)
This research aims to investigate the impact of Microsoft Power BI affects financial performance analysis in industrial firms in the Kurdistan Region of Iraq. As more businesses rely on big data and digital tools to make data-driven decisions, Power BI has become a popular business intelligence tool. The research addresses the lack of real evidence showing how Power BI helps with key financial areas including revenue, expenses, cash flow, profitability, financial health, and investment appraisal. To investigate this, a quantitative approach was used with a structured questionnaire sent to 20 industrial companies in Erbil, Sulaymaniyah, and Duhok. Out of 87 surveys sent, 78 valid responses were collected. The data was analysis using correlation and regression to examine how Power BI’s features like cost reduction, productivity improvement, and competitive advantage relate to financial performance. The results show that Power BI has a positive impact most financial areas, especially profitability, investment appraisal, and revenue. Among the features studied, competitive advantage had the strongest effect, while cost reduction had a smaller impact. In conclusion, the study shows that using Power BI to analysis big data in financial processes facilitates better decision-making, faster reporting, and stronger financial control. This highlights the value of BI tools for industrial firms in developing regions and suggests that more companies should adopt digital solutions for financial management.